Tebus Murah dan Perlindungan Hukum: Tinjauan Hukum Terhadap Hak Konsumen Dalam Transaksi Jual Beli - Muhtadli, Muhtadli; Pelangi, Intan; Taufiq, M. Shofwan; Pribadi, Adhimaz Kondang (Universitas Muhammadiyah Metro, 2025)
This study aims to analyze consumer rights and protection in the practice of discounted purchasing (tebus murah) and the perspective of Islamic law regarding such transactions. Discounted purchasing, which is increasingly popular among consumers, offers various benefits but also poses legal risks and challenges. In this context, the study identifies the consumer rights that need to be protected, including the right to clear and accurate information, as well as the right to receive goods that match what was promised. Furthermore, the research explores the legal protections available for consumers in Indonesia based on Law No. 8 of 1999 on Consumer Protection. The research employs a qualitative approach with data collection techniques through interviews, observations, and literature studies. The findings indicate that although there are regulations governing consumer protection, challenges remain in their implementation, especially in the digital context. This study is expected to provide recommendations for improving regulations and better business practices, as well as to enhance consumer awareness regarding their rights in discounted purchasing transactions.